NASA and the long civil rights movement - Odom, Brian C.; Waring, Stephen P. (University Press of Florida, 2019)
As NASA prepared for the launch of Apollo 11 in July 1969, many African American leaders protested the billions of dollars used to fund "space joyrides" rather than help tackle poverty, inequality, and discrimination at home. This volume examines such tensions as well as the ways in which NASA's goal of space exploration aligned with the cause of racial equality. Essays provide new insights into the complex relationship between the space program and the civil rights movement in the Jim Crow South and abroad. NASA and the Long Civil Rights Movement offers important lessons from history as today's activists grapple with the distance between social movements like Black Lives Matter and scientific ambitions such as NASA's mission to Mars.